2011
DOI: 10.1255/ejms.1116
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination of Drugs by DNA Tetranucleotides under Electrospray Ionisation Conditions

Abstract: The DNA tetranucleotides, extended versions of GCA at the 3'-end or 5'-end, were used as chiral selectors for the chiral discrimination of atenolol, DOPA, tamsulosin, valacyclovir and zolmitriptan. Chiral discrimination was achieved by investigating the collision-induced dissociation spectra of the [X+Y-2H](2-) ion generated by electrospraying a solution mixture of tetranucleotide (X) and R- or S-analyte drug (Y). The relative abundances of the precursor ion and the product ion, resulting from the loss of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Although innumerable studies covered the enantiomeric differentiation of amino acids applying the mass spectrometry methods, only a few studies described the enantiomeric differentiation of chiral drugs with amino alcohol functionality. There were some reports in the literature covering on the enantiomeric differentiation of drugs possessing amino alcohol functionality under ESI conditions . Jeminet et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although innumerable studies covered the enantiomeric differentiation of amino acids applying the mass spectrometry methods, only a few studies described the enantiomeric differentiation of chiral drugs with amino alcohol functionality. There were some reports in the literature covering on the enantiomeric differentiation of drugs possessing amino alcohol functionality under ESI conditions . Jeminet et al .…”
Section: Introductionmentioning
confidence: 99%
“…There were some reports in the literature covering on the enantiomeric differentiation of drugs possessing amino alcohol functionality under ESI conditions. [20,21] Jeminet et al reported the differentiation of enantiomeric phenylglycinol. [22] However, there is no systematic study on a series of β-amino alcohols derived from natural amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The CR value obtained for atenolol in the current study is higher than that of previous reports, while the value obtained for propranolol is comparable to that reported ( Table 1). [29,34] The CID spectra of the trimeric adduct ion obtained from enantiomers of atenolol are shown in Fig. 2.…”
Section: -Iodo-l-phenylalaninementioning
confidence: 99%
“…demonstrated the enantiomeric differentiation of DOPA using the fixed ligand method by selecting different biphenylic compounds as the fixed ligand . Recently, we reported differentiation of a set of chiral drugs by employing DNA tetranucleotide as the reference compound …”
mentioning
confidence: 99%
See 1 more Smart Citation